Integrated MCDM framework for sustainable pharmacy supplier selection using pioneering criteria with fuzzy TOPSIS SVR and GRA - R. Raveena; S. Umamaheswari (Scientific Reports)
Abstract Supplier selection is indispensable across diverse industries, particularly in the pharmaceutical sector, due to its direct impact on health and safety. This underscores the necessity for the timely availability of high-quality products. This research aims to elevate the sustainability of pharmaceutical inventory management by introducing pioneering criteria for supplier evaluation. A groundbreaking methodology is proposed by seamlessly integrating TOPSIS-GRA within a fuzzy environment for sustainable supplier selection. The CFCS algorithm ensures precise defuzzification, addressing uncertainties in data representation. Additionally, SVR improves criteria weighting by capturing complex data patterns. This integrated approach enables a comprehensive supplier assessment, offering valuable insights to pharmaceutical decision-makers. Ultimately, it provides a robust framework for selecting suppliers aligned with sustainability principles and optimizing procurement practices.